Peningkatan Hasil Belajar Bulutangkis Melalui Metode Latihan Pada Siswa Kelas VIII SMPN 1 Kabupaten Buru - makian, siti Faratasya; Jacob, Anaktototy; Unmehopa, Wilhelmina (MANGGUREBE: Journal Physical Education, Health and Recreation, 2023)
Increasing step learning outcomes to the Game of Badminton for Class VIII SMP Negeri 1 Kabupaten Buru. The Thesis of Physical Education Health and Recreation Program, in Faculty of Teacher Training and Education, Pattimura University. This research aims to improve the learning outcomes of back and forth movements in the game of badminton for class VIII SMP Negeri 1 Kabupaten Buru. This research uses a type of classroom action research where the data collection. The results explain that when the training method to learning the steps to change the badminton game, there is an increase in student learning outcomes. Suggestions for PJOK teachers that they can use the practice method, especially regarding the material on changing steps in the game of badminton at SMP Negeri 1 Kabupaten Buru.